2010
DOI: 10.1007/978-1-4419-7913-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-GPCRs in Tumorigenesis

Abstract: Alterations in the homeostasis of several adhesion GPCRs (aGPCRs) have been observed in cancer. The main cellular functions regulated by aGPCRs are cell adhesion, migration, polarity, and guidance, which are all highly relevant to tumor cell biology. Expression of aGPCRs can be induced, increased, decreased, or silenced in the tumor or in stromal cells of the tumor microenvironment, including fibroblasts and endothelial and/or immune cells. For example, ADGRE5 (CD97) and ADGRG1 (GPR56) show increased expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…aGPCRs are misregulated in developmental disorders and many cancers, and some aGPCRs are considered bona fide oncogenes (4)(5)(6)(7). This 33-member subclass of family B GPCRs is distinguished by large extracellular N termini that harbor various adhesion modules and a ∼320-aa GPCR autoproteolysis-inducing (GAIN) domain located proximal to the seven-transmembrane spanning domain (7TM) (8,9).…”
mentioning
confidence: 99%
“…aGPCRs are misregulated in developmental disorders and many cancers, and some aGPCRs are considered bona fide oncogenes (4)(5)(6)(7). This 33-member subclass of family B GPCRs is distinguished by large extracellular N termini that harbor various adhesion modules and a ∼320-aa GPCR autoproteolysis-inducing (GAIN) domain located proximal to the seven-transmembrane spanning domain (7TM) (8,9).…”
mentioning
confidence: 99%
“…Adhesion domains, which are thought to have adhesive properties, mainly exist in some adhesion molecules such as integrins, cadherins, and selectins. However, limited studies have shown that adhesion GPCRs are involved in the regulation of cell adhesion, motility, embryonic development, and immune response (12)(13)(14). GPR116, named Ig-hepta in the rat, is a member of the adhesion GPCR family.…”
Section: Introductionmentioning
confidence: 99%
“…in IRE1 signaling, using cells treated by tunicamycin (0.01 mg/ml during 2 hrs). Moreover, the proliferation rate of glioma cells with mutated IRE1 is decreased in 2 fold [30]. Thus, the blockade of both kinase and endoribonuclease activity of signaling enzyme IRE1 has significant effect on proliferation rate of glioma cells.…”
Section: Cell Culturementioning
confidence: 97%
“…It is overexpressed in various types of tumors and its overexpression is believed to promote cancer progression [26] [27] [28] [29]. ADGRE5 (CD97 antigen) mediates cell-cell interactions, which is involved in angiogenesis and cell migration and is also overexpressed in many cancers [30]. The expression of ADGRE5 gene may play a role in the progression of several types of cancer [31].…”
mentioning
confidence: 99%